Cephalopods as vectors of harmful algal bloom toxins : a toxicokinetic and ecophysiological approach - Lopes, Vanessa M. (2020)
Tese de doutoramento, Ciências do Mar, Universidade de Lisboa, Faculdade de Ciências, 2018